2020
DOI: 10.3855/jidc.12087
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak investigation of septicemic salmonellosis in calves

Abstract: Introduction: An early and accurate diagnosis of septicemic salmonellosis is critical for implementing timely and proper treatment, prevention, and control measures. Methodology: Here, we report a study on three outbreaks of septicemic salmonellosis in calves from Midwestern Brazil. Results: the morbidity, mortality and lethality rates were of 10.55%, 2.79%, and 26.4%, respectively. Higher susceptibility was detected in Bos taurus than in Bos indicus cattle. Clinical manifestations consisted of apa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Salmonella has the ability to adapt to a variety of animal hosts, and to humans, and can be transmitted through contaminated food such as eggs, meat, raw vegetables, or through water [29]. More specifically, bovine salmonellosis is responsible for public and animal health problems and serious economic losses due to high mortality, and is often caused by Salmonella Dublin [11,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salmonella has the ability to adapt to a variety of animal hosts, and to humans, and can be transmitted through contaminated food such as eggs, meat, raw vegetables, or through water [29]. More specifically, bovine salmonellosis is responsible for public and animal health problems and serious economic losses due to high mortality, and is often caused by Salmonella Dublin [11,30].…”
Section: Discussionmentioning
confidence: 99%
“…Infected animals may develop symptoms or shed Salmonella in their feces without showing any clinical signs of disease. Clinical manifestations of bovine salmonellosis include mainly apathy, hyperthermia, difficulty breathing, panting, pallor of the mucous membranes, and forthe most commonly reported manifestation, abortion [10,11]. The risk associated with asymptomatic carriage is that cattle may introduce this organism into an abattoir, which can represent a significant food safety hazard of cross-contamination during food processing [8].…”
Section: Introductionmentioning
confidence: 99%
“…Guizelini et al and Salaheen et al found that most serovars of Salmonella spp. can infect and cause disease in cattle, leading to direct economic losses in the dairy industry associated with mortality or body weight loss, in addition to indirect losses caused by reduced feed conversion or medical care costs [ 52 , 53 , 54 ]. More than 90% of yaks in the world live in China and provide local residents with meat, dairy products, transportation, and fuel, which are vital to the meat and dairy production system in high-altitude regions [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…techniques, such as polymerase chain reaction (PCR), are useful tools for investigating cases of salmonellosis, especially in cases of low bacterial count; therefore, this diagnostic method may help to identify carriers of the disease (MOUSSA et al, 2010;GUIZELINI et al, 2020). Nonetheless, in this study, IHC was used to confirm Salmonella spp.…”
Section: Molecularmentioning
confidence: 96%